Guardianship or Partnership? Status of Wife and Property Co-ownership of Spouses in Medieval Brno (Theatrum historiae, 2018)
The text focuses on position of a wife in medieval urban milieu using medieval Brno as a case example. In addition to her legal status, which is reconstructed based on the analysis of valid legal norms, we pay attention mainly to the concept of property coownership of spouses and its functioning in everyday life, about which we can learn based on written cases that were part of the common agenda of the city council, that is gathered in the socalled Memorial Books.
Keywords: Middle Ages; urban; law; marriage; property coownership of spouses; gender history